2001
DOI: 10.1177/00912700122010555
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide Dose Proportionality Assessment following Single Doses to Healthy Subjects

Abstract: Thalidomide is approved in the United States for treating erythema nodosum leprosum, a complication of leprosy. The present study determined the single-dose oral pharmacokinetics and dose proportionality from 50 to 400 mg of Celgene's commercial Thalomid thalidomide formulation in an open-label, single-dose, three-way crossover study. Fifteen healthy subjects were given 50, 200, and 400 mg of thalidomide on three occasions, and blood samples were collected over 48 hours. Pharmacokinetic parameters were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…We considered this discrepancy was because our analyses placed the highest prior- Acute bronchitis ity on avoiding adverse events to continue the treatment. As well as previous studies, 10,16) this study was conducted in daytime although thalidomide is usually administered before bedtime. In the approved protocol, we gave priority to frequent full sampling on the initial two days, and were unable to obtain samples another time due to reducing the burden of excessive sampling for patients.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…We considered this discrepancy was because our analyses placed the highest prior- Acute bronchitis ity on avoiding adverse events to continue the treatment. As well as previous studies, 10,16) this study was conducted in daytime although thalidomide is usually administered before bedtime. In the approved protocol, we gave priority to frequent full sampling on the initial two days, and were unable to obtain samples another time due to reducing the burden of excessive sampling for patients.…”
Section: Discussionmentioning
confidence: 81%
“…Although we did not evaluate AUC 0-∞ at a dose of 200 mg, we expect that AUC 0-∞ at a dose of 200 mg may be double that at a dose of 100 mg, taking into consideration that AUC 0-∞ increased proportionally with doses from 50 to 400 mg in healthy male subjects. 16) Thus, we speculated that, at 200 mg dosing, patients D, E and F suffered adverse events because their AUC 0-∞ was above 23-24 mg · h/ml, while patients G and H did not suffer adverse events because their AUC 0-∞ was approximately equal or below the cutoff value (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a primary arylamine group and carbonyl group on the phthaloyl ring, in addition to the imide group on the glutamic ring may result in better aqueous solubility of lenalidomide compared to thalidomide. This notion is supported by the pharmacokinetic observation that, unlike thalidomide, lenalidomide does not seem to undergo absorptionrate limited absorption (flip-flop pharmacokinetic profile) at clinically achievable doses [12].…”
Section: Structure and Physicochemical Proper-tiesmentioning
confidence: 94%
“…Thal consist of an racemic mixture of S(-) and R(+) enantiomers. The enantiomers can rapidly interconvert at physiologic pH and have different biologic effects-the S-enantiomer being primarily responsible for the teratogenic effects and the R-enaniomer for the sedative properties [14][15][16]. This finding indicated that purification of the R(+) isoform, although less effective in its ability to suppress TNF expression and antiangiogenic properties, would be a safer way for the usage of Thal.…”
Section: Chemistry and Pharmacokineticsmentioning
confidence: 99%